2018
DOI: 10.1007/s11019-018-9873-7
|View full text |Cite
|
Sign up to set email alerts
|

Me? The invisible call of responsibility and its promise for care ethics: a phenomenological view

Abstract: Care ethics emphasizes responsibility as a key element for caring practices. Responsibilities to care are taken by certain groups of people, making caring practices into moral and political practices in which responsibilities are assigned, assumed, or implicitly expected, as well as deflected. Despite this attention for social practices of distribution and its unequal result, making certain groups of people the recipient of more caring responsibilities than others, the passive aspect of a caring responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…From each of the found appearances of feeling called, it becomes clear that caring situations are, as care ethicists argue, “situations that are given to us, that we find ourselves in, as a consequence of being related” (p. 527) [ 34 ]. The families in this study often found themselves embedded in practices in which they felt called and responsible to care [ 19 ]. Our results suggest that – rather than in feeling called per se – the burden of care might lie in the seeming limitlessness to which people feel called, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From each of the found appearances of feeling called, it becomes clear that caring situations are, as care ethicists argue, “situations that are given to us, that we find ourselves in, as a consequence of being related” (p. 527) [ 34 ]. The families in this study often found themselves embedded in practices in which they felt called and responsible to care [ 19 ]. Our results suggest that – rather than in feeling called per se – the burden of care might lie in the seeming limitlessness to which people feel called, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies sometimes show average or median hours of family caregiving per week to indicate burden [ 11 ], but invested time is not the only issue nor the most relevant. Caregiving is complex, as we have shown by providing more insight into the inherent normative nature of family caregiving, and is also deeply connected to one’s social, cultural, and political context and related feelings of power [ 19 ]. Revealing this complexity to caregivers gives counterweight to dominant expectations [ 32 ], and may enable them to talk about their seemingly inappropriate experiences or feelings – whether negative or positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Partners or family members often find themselves in the role of family caregiver because they are related to the patient. 3 , 4 Many family caregivers (hereafter: caregivers), however, live in permanent uncertainty about the future, while feeling unprepared for their caring role 5 7 and overwhelmed by the demands of the all-consuming nature of caring. 8 Previous research showed how caregiving impacts normal daily life and social engagements, 2 , 7 , 9 causing physical, emotional, and psychosocial challenges that demand support.…”
Section: Introductionmentioning
confidence: 99%